Phospholipid Degradation in Frozen Plant Cells Associated with Freezing Injury - Yoshida, Shizuo (1974)
A striking degradation of phosphatidylcholine into phosphatidic acid was observed in the cortical tissues of less hardy poplar (Poplus euramericani cv. gelrica), when the tissues were frozen below a lethal temperature. No change in phospholipids was detected during freezing or even after thawing in the cortical tissues of hardy poplar which survived slow freezing to −30 C or even immersion in liquid N(2) after prefreezing to −50 C. The degradation of phosphatidylcholine during freezing appears to be intimately associated with freezing injury.